Influence of quartz and phosphorus impurities on hydration process and early-age properties of sustainable excess-sulphate phosphogypsum slag cement - Tao Sun; Yihua Deng; Gaoshang Ouyang; Ziyan Wang; Juntu He; Minglong Chen (Case Studies in Construction Materials)
Excess-sulphate phosphogypsum slag cement (EPSC), incorporating 40–60 % phosphogypsum (PG), offers a sustainable solution for phosphogypsum disposal while stabilizing hazardous impurities. However, typical impurities in phosphogypsum, such as quartz and phosphorus, significantly impede the hardening kinetics and compromise early strength development of EPSC, thereby constraining its practical application. The influence of quartz on EPSC properties was investigated using quartz with particle size distributions analogous to those found in phosphogypsum. By employing HNO3 to modulate gypsum pH, the impact of initial alkalinity on EPSC hydration was systematically examined, followed by an in-depth analysis of phosphate doping effects on the hardening and hydration mechanisms. Results revealed that substituting 10.42 % gypsum with quartz in EPSC maintains supersaturated sulfate concentrations, exerting negligible influence on hydration processes. While initial pH suppression transiently inhibited early dissolution of ground granulated blast-furnace slag (GGBS), no long-term interference was observed. Phosphate impurities impair gypsum's dissolution-crystallization equilibrium via Ca2+ sequestration, evidenced by 42.9 % suppressed Ca2+ release and 14.6 % crystallite coarsening during initial hydration stages. The results show that phosphorus impurities can affect the dissolution and crystal morphology of gypsum and the hydration of cement clinker, delay the activation of GGBS, and seriously affect the condensation and hardening of EPSC.